2021
DOI: 10.1371/journal.pone.0248011
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses to folic acid in an established keloid fibroblast cell line are mediated by JAK1/2 and STAT3

Abstract: Keloids are a type of disordered scar formation which not only show heterogeneity between individuals and within the scar itself, but also share common features of hyperproliferation, abnormal extra-cellular matrix deposition and degradation, as well as altered expression of the molecular markers of wound healing. Numerous reports have established that cells from keloid scars display Warburg metabolism—a form of JAK2/STAT3-induced metabolic adaptation typical of rapidly dividing cells in which glycolysis becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
7
1
Order By: Relevance
“…Alterations in mitochondrial phosphorylated STAT3 found in KFs, limiting oxidative phosphorylation, was suggested as an explanation for this contradictory finding. Finally, the authors of this study suggested a possible role for folate metabolism in keloids pathogenesis mediated by JAK1/2 and STAT, 17 which has not been described in other studies.…”
Section: Resultsmentioning
confidence: 46%
See 3 more Smart Citations
“…Alterations in mitochondrial phosphorylated STAT3 found in KFs, limiting oxidative phosphorylation, was suggested as an explanation for this contradictory finding. Finally, the authors of this study suggested a possible role for folate metabolism in keloids pathogenesis mediated by JAK1/2 and STAT, 17 which has not been described in other studies.…”
Section: Resultsmentioning
confidence: 46%
“…No additional studies were retrieved with reference list checking. Thirteen studies reported experiments with JAK and/or STAT inhibitors 8,14,15,17–26 . Seven studies reported on JAK and/or STAT expression in (keloid) cells or tissues without involving drug testing 9,27–32 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From a metabolic viewpoint, keloids exhibit accelerated glycolysis reminiscent of Warburg metabolism, a unique adaptive state presumably induced by JAK2/STAT3 ( 50 , 221 ). Interestingly, an in vivo study demonstrated regulation of keloid fibroblast activity at the cost of a worsened hyperglycolytic state with JAK1/2 blockade ( 222 ). Epigallocatechin-3-gallate (EGCG), a green tea extract, has been found to possess chemopreventive properties, including suppression of STAT3 signaling, potentially inhibiting keloid growth ( 219 ).…”
Section: Key Cytokine Pathways In Keloid Formationmentioning
confidence: 99%